The Earliest T-Precursors in the Mouse Embryo Are Susceptible to Leukemic Transformation - Ding, Jixin; Cardoso, Angelo A.; Yoshimoto, Momoko; Kobayashi, Michihiro (Frontiers in Cell and Developmental Biology, 2021)
Acute lymphoblastic leukemia (ALL) is the most common malignancy in pediatric patients. About 10-15% of pediatric ALL belong to T-cell ALL (T-ALL), which is characterized by aggressive expansion of immature T-lymphoblasts and is categorized as high-risk leukemia. Leukemia initiating cells represent a reservoir that is responsible for the initiation and propagation of leukemia. Its perinatal origin has been suggested in some childhood acute B-lymphoblastic and myeloblastic leukemias. Therefore, we hypothesized that child T-ALL initiating cells also exist during the perinatal period. In this study, T-ALL potential of the hematopoietic precursors was found in the para-aortic splanchnopleura (P-Sp) region, but not in the extraembryonic yolk sac (YS) of the mouse embryo at embryonic day 9.5. We overexpressed the Notch intracellular domain (NICD) in the P-Sp and YS cells and transplanted them into lethally irradiated mice. NICD-overexpressing P-Sp cells rapidly developed T-ALL while YS cells failed to display leukemia propagation despite successful NICD induction. These results suggest a possible role of fetal-derived T-cell precursors as leukemia-initiating cells.